(untitled) (Sains Humanika, 2018)
The implementation of teaching and learning through the use of technology helped in interactive and interesting delivery of knowledge. The transformation from traditional learning now students learn through Virtual Learning Environment (VLE) can attract interest apart from a wide material access by the students. The implementation of learning through Halaman Celik Akal gives positive impact towards students’ motivation, attitude and performance especially in Malay language subject. This purpose of this research is to review students’ motivation and attitude and also investigate the relationshiop between both constructs. This research focused on students’ performance after using this page in teaching and learning. This research involved 31 students of Standard 5 in Primary School. There are four questions being analysed in this research. The finding of this research shows that students’ motivation and attitude are at a high level after learning through this page. From the performance aspect shows that there are differences between students’ score before and after using this page (t= -8.162, df=30, p = 0.00). However, the findings of this research shows that there no relationship between students’ motivation and attitude (R= -0.059, P = 0.752) through this learning. Therefore, this research shows that the implementation of Virtual Learning Environment (VLE) through virtual page has a lot of benefits to the students especially in the aspect of students’ motivation, attitude and performance in learning Malay language.